Model Service Quality : Case Study Indonesian Domain - Suryawan, Ryan Firdiansyah; Candra Susanto, Primadi; Agusinta, Lira (Dinasti International Journal of Digital Business Management, 2024)
Domain Internet Indonesia this study aims to determine the price for the loyalty of .id domain users name, the quality of user loyalty, and brand image on the loyalty of .id domain users name. The sample of this study amounted to 93 taken from the Lemeshow formula with an alpha of 5% of the total customers who did not renew the .id domain name at the Indonesian Internet Domain name manager  This research method uses quantitative methods with Structural Equation Modeling (SEM): Partial Least Square (PLS). This research was conducted by developing a model to analyze the effect of price, brand image, and product quality on consumer loyalty for .id domain names. The researcher describes the results found, then proceeds with discussing the conclusions of acceptance or rejection of the hypothesis as well as various theoretical and managerial implications that arise and will present the limitations of the research  and  future agenda that can be carried out as a continuation of research on the .id domain.